Rainwater, a tool for development and maintenance of nature in the city - Three development projects illustrating the water as a support of natural processes in urban environment - Piel, Christian (project baikal, 2013)
The problems of manage urban stormwater are gradually taken into account by planners and landscapers. If the ecological potential of the temporary retention techniques is correctly operated in peri-urban areas, it is too little valued in a dense urban environment. Dense urban environment where the demand of nature is becoming stronger.Presented three projects in dense urban areas, where rainwater is treated as support nature, and as a factor in natural processes.These projects also aim to show how the problem of flood is a support social, legal, and financial, to implement these natural processes, so necessary in urban areas.
Keywords: flood park; reed; blue frame; green frame; bioclimatology; biodiversity; rain garden; floating garden; pool; grant governance